Growth and Late Detection of Post-Operative Cholesteatoma on Long Term Follow-Up With Diffusion Weighted Magnetic Resonance Imaging (DWI MRI): A Retrospective Analysis From a Single UK Centre. Issue 5 (June 2019) - Pai, Irumee; Crossley, Eleanor; Lancer, Hannah; Dudau, Cristina; Connor, Stephen
Abstract : Objective: To evaluate the growth rate and late detection of residual cholesteatoma on long-term follow-up with diffusion weighted magnetic resonance imaging (DWI MRI) in clinically stable ears following definitive surgery, in order to define surveillance imaging protocols. Study Design: Retrospective case review. Setting: Tertiary referral center. Patients: Patients who underwent DWI MRI at our institution between February 2007 and May 2013 for postoperative cholesteatoma follow-up. Intervention: Non-echo planar imaging (non-EPI) Half-Fourier Acquisition Single-shot Turbo spin Echo (HASTE) DWI MRI. Main outcome measures: Intervals between the definitive surgery and the first and subsequent DWI MRI, the maximum coronal dimension of the lesion on DWI and length of follow-up. Results: The study evaluated 152 postoperative DWI studies performed for 88 patients. In 12 cases, DWI was initially negative but became positive on repeat imaging after a mean interval of 3.8 years from the initial cholesteatoma surgery (median 3.7 years, range 1.6–7.9). Of these, 3/12 had more than one negative/indeterminate DWI before disease was eventually detected on imaging; in this subgroup, the mean interval between surgery and positive DWI was 3.2 years (median 2.6 years, range 2.3–4.2). 39 DWI positive foci with serial imaging demonstrated a mean growth rate of 4 mm/year (median 2 mm, range 0–18). Conclusions: After negative initial DWI, it is proposed that interval imaging should be considered for a minimum of 5 years in stable ears following definitive cholesteatoma surgery. In view of the marked variability in growth rate, an additional interval scan between 2 and 3 years postoperatively is indicated.